Global Dynamics of a Periodic SEIRS Model with General Incidence Rate - Eric Ávila-Vales; Erika Rivero-Esquivel; Gerardo Emilio García-Almeida (International Journal of Differential Equations)
We consider a family of periodic SEIRS epidemic models with a fairly general incidence rate of the form Sf(I), and it is shown that the basic reproduction number determines the global dynamics of the models and it is a threshold parameter for persistence of disease. Numerical simulations are performed using a nonlinear incidence rate to estimate the basic reproduction number and illustrate our analytical findings.